The Art of Goodbye: Exploring Self-Reflection - Lynda Spence; Chelsea Tafelski (EDIS)
Many people assume that preparing for the end of life involves filling out forms at the doctor’s or lawyer’s office. Forms and checklists have their place and can be helpful, but they cannot address every issue because end-of-life concerns are complicated. Self-reflection is a helpful tool that begins to lay a foundation for planning while articulating people’s complex and unique emotions, values, priorities, fears, and preferences when it comes to facing their own mortality. This 4-page fact sheet is the second publication in a series entitled The Art of Goodbye: End of Life Education series, and it covers resources that can help individuals explore their personal concerns and values before initiating end-of-life discussions with loved ones. Written by Lynda Spence and Chelsea Tafelski, and published by the UF Department of Family, Youth and Community Sciences, October 2016.